"Looking Forward Always to Africa": William George Emanuel and the Politics of Repatriation in Cuba, 1894–1906. Issue 1 (January 2021) - Janzen, Philip
Abstract: This article examines a back-to-Africa movement from early twentieth-century Cuba. The leader, William George Emanuel, arrived in Cuba from Antigua in 1894, and over the next several years, he worked to unite the cabildos de nación and sociedades de color on the island. After independence in 1898, Emanuel and his followers rejected Cuban citizenship and began petitioning Britain, the United States, Belgium, and the Gold Coast for land grants in West and Central Africa. Each petition, however, told a different story. Emanuel skillfully tailored his appeals according to his audience, variously claiming that he and his followers were "British, " "African, " "Congolese, " or "Mina, " among other identities. Anticipating the rise of Marcus Garvey by over a decade, Emanuel's campaign reveals an overlooked pan-Africanist strand in the typical narrative for this period of Cuban history. Drawing mainly on the petitions themselves, the article analyzes how Emanuel blended the languages of empire, nation, race, and ethnicity to create a dynamic pan-African identity. More generally, the article demonstrates how marginalized groups have long negotiated the boundaries of identity in the pursuit of belonging.